What Shapes Satisfaction with Democracy? Interests, Morals, and the German East–West Divide - Heinz Welsch (Social Indicators Research, 2022)
Thirty years after reunification, East and West Germany are still characterized by a considerable difference in satisfaction with democracy (SWD). This paper proposes and tests a model which assumes SWD to be shaped by the interests (economic and cultural) and moral values individuals demand to see fostered by the democratic system. Empirical application of the model reveals substantial differences between the East and West German SWD function in that the satisfaction of economic interests is much more important in the East than the West whereas the opposite applies to moral concerns. Demands on redistribution and immigration policies—conceptualized as proximate drivers of SWD—also shape SWD differently in the East and the West, in addition to being shaped by interests and morals in different ways. East–West differences in the relationship between economic demands and SWD are more important than differences in the levels of demand.
Keywords: P51; E24; J08; A13; 300; Satisfaction with democracy; Communist legacy; Employment; Income; Morals; Germany